CHEMICAL MODIFICATION OF FARM-GROWN EUCALYPTUS WOOD TO REDUCE SEASONING DEFORMITIES - Zahid, Din Muhammad; Khan, Zahoor Hussain; Quraishi, Masood A. A. (Journal of Research (Science), 2001)
In an attempt to overcome seasoning defects in wood the green sawn members of Eucalyptus camaldulensis Dehn. were treated with different chemical solutions. To start with, the wood specimens were submerged in 35% solutions of DEG, sucrose, zinc sulfate, sodium silicate, ferrous ammonium sulfate, 5% solutions of alginate and pure diesel oil for one week. DEG and sucrose were better than other chemicals to minimize the seasoning defects. Both DEG and sucrose are easily available and have encouraging use to control shrinkage and warpage. The effect of DEG solution expressed as ASE (%) on periphery (girth), and over the total volume were 31% and 25% respectively and expressed as LRF (%) on bend, twist, and overall volume were 99%, 95%, and 93% respectively. The effects of treatment with sucrose solution on shrinkage in girth and volume expressed as ASE were 28% and 23% respectively and expressed as LRF for bend, twist and overall volume recovery were 99%, 92% and 90% respectively after treating with the sucrose. It is of practical importance that DEG and sucrose are economical and easily available chemicals.